2007
DOI: 10.1111/j.1743-6109.2007.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lead Exposure May be Associated with Erectile Dysfunction

Abstract: Introduction Heavy metals constitute significant potential threats to human health in both occupational and environmental settings. Research examining the etiology of lead toxicity-induced hypertension reveals that the free radical production and lowering of inherent antioxidant reserves resulting from lead toxicity are directly related to vasoconstriction underlying lead-induced hypertension. A similar mechanism would affect smooth muscle relaxation in the cavernous tissue leading to erectil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Smoking was presented as a significant risk factor for ED by Elbendary et al (2009) in their comparison of 434 patients with ED and 272 patients as controls under 40 years old, and a negative correlation between smoking index and IIEF-5 scores of patients with ED was detected. Some studies suggested cut-off values between 20 and 30 lg dl À1 and these studies accepted lead intoxication as over these values (Murata et al, 1993;Sokas et al, 1997;Lustberg & Silbergeld, 2002;Anis et al, 2007). In our study, the mean age was under 40 years old and smoking was a risk factor for ED in both groups of patients.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Smoking was presented as a significant risk factor for ED by Elbendary et al (2009) in their comparison of 434 patients with ED and 272 patients as controls under 40 years old, and a negative correlation between smoking index and IIEF-5 scores of patients with ED was detected. Some studies suggested cut-off values between 20 and 30 lg dl À1 and these studies accepted lead intoxication as over these values (Murata et al, 1993;Sokas et al, 1997;Lustberg & Silbergeld, 2002;Anis et al, 2007). In our study, the mean age was under 40 years old and smoking was a risk factor for ED in both groups of patients.…”
Section: Discussionsupporting
confidence: 45%
“…Ghazi-Khansari et al (1997) reported that lead intoxication reduced bromocriptine-induced penile erection response in rats. Anis et al (2007) reported that oxidative stress increased in lead intoxication, and similar changes with vascular ED could be observed in the corpus cavernosum of patients with lead intoxication. Anis et al (2007) reported that oxidative stress increased in lead intoxication, and similar changes with vascular ED could be observed in the corpus cavernosum of patients with lead intoxication.…”
Section: Discussionmentioning
confidence: 57%
“…Decreased libido is secondary to altered hypothalamic-pituitary axis and altered orgasm [13]. Sexual symptoms in the case reported here included poor libido, unable to get a penile erection, ejaculatory and orgasmic dysfunction due to pelvic autonomic neuropathy secondary to lead poisoning [14,15].…”
Section: Discussionmentioning
confidence: 67%
“…Pb in gasoline emissions (cases exposed =169) was not associated with increased risk of prostate cancer (OR, 0.9; 95% CI 0.7-1.2). It is widely known that the male reproductive system is adversely affected by Pb [67,68], and Pb has been associated with poorer sperm quality[69] and erectile dysfunction [70]. Higher PSA levels have also been reported to be associated with Cd [71] and with Pb [72] exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that although old housing is best known for Pb exposure, small quantities of Cd are contained in house paint [76]. Finally, Pb exposure has been associated with erectile dysfunction [70] and male fertility [14], two variables we did not have in our data set. We did control for benign prostatic hyperplasia which did not change results appreciably.…”
Section: Discussionmentioning
confidence: 99%